AN OVERVIEW OF PARENTS READINESS IN SUPPORTING LEARNING FROM HOME FOR EARLY CHILDHOOD DURING THE COVID-19 PANDEMIC PERIOD - Ismaniar Ismaniar; Sri Murni (PEDAGOGIA, 2022)
This research is motivated by the many complaints about the lack of optimal learning stimulation activities for early childhood during the pandemic, even though early childhood is the golden age of every child's development and affects the development of children at a later age. The study aims to describe the readiness of families, especially parents, to support learning stimulation activities from home during the pandemic in terms of the readiness of the knowledge and skills needed, the readiness of infrastructure to support children's learning from home, and the readiness to provide mentoring time during the implementation of learning stimulation from home. This research is quantitative and descriptive. Data collection was carried out using a questionnaire technique distributed online using the Google Form application. The data analysis technique uses the percentage formula. Data collection involved 450 respondents randomly representing five provinces; West Sumatra, West Java, Central Java, East Java, and Gorontalo. Based on the study's results, it was concluded that; 1). In general, families (parents) of early childhood do not have the knowledge and skills to support children's learning activities from home. 2) In general, families (parents) of early childhood do not have adequate infrastructure to support children's learning activities from home. 3) In general, families (parents) of early childhood do not have the readiness to provide time and opportunities for assistance during activities to study children from home.